Developmental regulation of a Rhizobium cell surface antigen during growth of pea root nodules. - VandenBosch, K A (1989)
A monoclonal antibody, AFRC MAC 203, was used to examine the expression of a nodule-induced cell surface antigen associated with lipopolysaccharide in Rhizobium leguminosarum bv. viciae 3841. Silver-enhanced immunogold-labeled tissue sections revealed that, in very young tissues of pea root nodules, the nodule-induced form of lipopolysaccharide antigen was not expressed either by rhizobia in the infection thread or by bacteria recently released into the plant cell cytoplasm. In the more mature regions of the nodule, the antigen was expressed by membrane-enclosed bacteroids, including immature forms that had not yet expressed the enzyme nitrogenase and were not yet Y shaped. Immunogold labeling of thin sections revealed that the MAC 203 antigen, but not the nitrogenase, was also expressed by bacteria in infection threads situated in and between bacteroid-containing plant cells in mature nodule tissue.